METHODS AND TECHNIQUES OF FINANCIAL CONDITION’ ANALYSIS: FEATURES USE FOR SMALL ENTERPRISES - Гриценко, Лариса; Боярко, Ірина (Socio-economic relations in the digital society, 2019)
In modern economic conditions, each enterprise must provide itself with the appropriate amount of financial resources necessary for the conduct of economic activity. The degree of financial resources availability depends to a large extent on the financial condition of the enterprise, which is the most important characteristic of the production and financial activity of the enterprise. To analyze the financial condition of the company, there are many methods and techniques developed by a number of scientists. Methods of calculating the indicators,which are fixed in the normative documents of different ministries and departments, as well as presented in various scientific developments, vary significantly, which results in the absence of a single approach to assessing the financial condition. The aim of the article is to investigate the basic methods and techniques for the analysis of small enterprises’ financial condition and justify the feasibility of using them. The results of the research.The definitions of concepts «financial condition» and «financial analysis» are systematized and generalized, and their author’s interpretation is proposed. The content analysis of the definition of the term «financial analysis» is done. A detailed analysis of the main methods and techniquesfinancialcondition’ analysisis suggested, their characteristics are given, advantages and disadvantages are presented. The feasibility and the peculiarities of the use of certain methods and techniques for the analysis of small enterprises’ financial condition are investigated. Most methods and techniques financial condition’ analysis are based on coefficient analysis. There is a need to develop a differentiated approach to establishing the normative values of financial indicators for enterprises of different types of economic activity. Further research is important to focus on the development of methodical approaches to the analysis of enterprises’ financial conditionon the basis of deviations’ factor analysis of the main result indicators of theenterprise activity and recommendations on the formation of strategic development guidelines.
Keywords: financial condition; financial analysis; analysis of financial condition; complex estimation of financial condition; method of coefficient analysis; financial result